Effect of Web navigation style in elderly users. (February 2016) - Castilla, Diana; Garcia-Palacios, Azucena; Miralles, Ignacio; Breton-Lopez, Juana; Parra, Elena; Rodriguez-Berges, Sergio; Botella, Cristina
Abstract: The population is gradually aging, but only 4% of elderly people are Internet users. These data indicate the need to take action to bridge this digital divide. Several studies show that learning and memory processes are faster when there is familiarity with the learning object, and the user finds a clear internal correspondence between the previous experience and the current experience. The elderly make up one of the groups most affected by the digital divide, with less Internet access, knowledge, and use. The Internet is by definition an almost infinite structure of hypertext, where the user navigates by using information in an active way, and where the elderly lack previous experience with hypertextual applications. The aim of this study is to test the navigation variable by comparing two designs of the same email Web application with different navigation styles: linear vs hypertextual navigation. The study consisted of usability testing, employing the method of task analysis. Other assessment tools were also used, such as the eye tracker and post-session self-report questionnaires designed ad hoc for this study. A sample of 34 users from 60 to 83 years old and with heterogeneous previous experience with new technologies participated in the study. They performed A/B testing with a counterbalanced within-subject design. The linear navigation condition, compared to the hypertextual condition, obtained a higher success rate, lower performance time, better satisfaction ratings and greater user preference. The main contribution of this study is to demonstrate the relevance of navigation in systems oriented toward the elderly, indicating that linear navigation is more suitable for these users. Highlights: We designed two versions of the same webmail linear vs hypertextual navigation. We tested both versions with elderly users. The linear navigation obtained better usability and preference results. The linear navigation obtained a higher success rate than hypertextual navigation. Users obtained a lower performance time with the linear navigation.